Management of Varicose Veins and Chronic Venous Insufficiency in a Comparative Registry with Nine Venoactive Products in Comparison with Stockings - Belcaro, G.; Dugall, M.; Luzzi, R.; Corsi, M.; Ledda, A.; Ricci, A.; Pellegrini, L.; Cesarone, M. R.; Hosoi, M.; Errichi, B.M.; Cornelli, U.; Cotellese, R.; Agus, G.; Feragalli, B. (International Journal of Angiology, 2017)
The aim of this registry study was to compare products used to control symptoms of CVI. Endpoints of the study were microcirculation, effects on volume changes, and symptoms (analogue scale). Pycnogenol, venoruton, troxerutin, the complex diosmin-hesperidin, Antistax, Mirtoselect (bilberry), escin, and the combination Venoruton-Pycnogenol (VE-PY) were compared with compressions.No safety or tolerability problems were observed. At inclusion, measurements in the groups were comparable: 1,051 patients completed the registry. Best performers: Venoruton, Pycnogenol, and the combination VE-PY produced the best effects on skin flux. These products and the combination VE-PY better improved PO2 and PCO2. The edema score was decreased more effectively with the combination and with Pycnogenol. Venoruton; Antistax also had good results. Considering volumetry, the best performers were the combination PY-VE and the two single products Venoruton and Pycnogenol. Antistax results for edema were also good. The best improvement in symptoms score were obtained with Pycnogenol and compression. A larger decrease in oxidative stress was observed with Pycnogenol, Venoruton, and with the VE-PY combination. Good effects of Antistax were also observed. Parestesias were lower with Pycnogenol and with Antistax. Considering the need for interventions, the best performers were Pycnogenol, VE-PY, and compression. The efficacy of Pycnogenol and the combination are competitive with stockings that do not have the same tolerability in warmer climates. A larger and more prolonged evaluation is suggested to evaluate cost-efficacy (and non-interference with drugs) of these products in the management of CVI. The registry is in progress; other products are in evaluation.
Keywords: chronic venous insufficiency; venous disease; varicose veins; elastic stockings; venoactive compounds; edema